Instructional Materials Motivation and Synchronous Classroom Learning in Relation to the Students' Academic Performance in Mathematics - Kristine Mae Sabayton; Rosa Mae Alvarado; Joicelyn Bacus; Genelyn Baluyos (PT ARRUS Intelektual Indonesia, 2023)
Students’ motivation and perception are important factors to consider in online learning. This study determined the students’ level of motivation in instructional materials and perception in synchronous classroom learning at Misamis University for the academic year 2021-2022. The researchers used the descriptive-correlational research design. The respondents of the study were the 138 Junior High School students chosen through purposive sampling technique. The gathering of data was done by the use of the Instructional Materials Motivation Survey (IMMS) and Synchronous Classroom Learning Survey (SCLS) as instruments. Mean, Standard Deviation, Pearson r, and Stepwise Regression Analysis were the statistical tools employed in the data analysis. Results revealed that students' level of motivation in instructional materials used by teachers was high, and students' perception of synchronous classroom learning was good. This indicates that students who find the learning materials appealing are more likely to perform well in Mathematics. Teachers needed to be comfortable using technology to produce classes, interactive activities, assessments, projects, and other responsibilities to boost their creativity in creating instructional materials to increase students' satisfaction in the classroom. Future researchers should look into other factors contributing to students' academic performance in synchronous classroom learning.